(3MGTjI Ydi TQM GdJaJGRGfj ddYbGFO GdfSajIs - (3GdMfaj, CafOj, QeVGf Hf eMeOs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj JhMO HGdYXeI hHYO jbhd QeVGf Hf eMeO GdMfaj deG QCjJ GdeNJUQ GdeTghQ HTQM GdYbGjO ddTjN SYO GdedI hGdOjf CQOJ Cf CTQM TQMGs
(3BNQgG (B:s
(3GdBKGQ GdbhjI dG aj eWdb GdTQa aj GddZI GdecGf GdeQJaY GdYGdj hGdceGd adG OdGdI Ydi CaVdjI GdedGFcI Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B2 / 1145s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds